الوسيط في المواد الجزائية طبقا للتشريع الجزائري والفرنسي - فتحي دريس, كمال (جامعة الوادي University of Eloued, 2017)
إستحدث المشرع الجزائري بموجب الأمر رقم (15/02) المؤرخ في 23/07/2015، المعدل لقانون الإجراءات الجزائية وقانون حماية الطفل رقم (15/12) المؤرخ في 15/07/2015، نظام الوساطة باعتباره آلية جديدة لحل النزاعات في بعض المواد الجزائية، وذلك مواكبة للتشريعات سواء الكومن لو أو الرومانو- جرمانية، التي أخذت بها منذ أمد بعيد. وتضم عملية الوساطة ثلاثة أطراف، الضحية المشتكى منه والوسيط، هذا الأخير الذي أسندت إليه مهمة إدارتها، محاولا تقريب وجهات نظر الطرفين للوصول إلى اتفاق ينهي النزاع وتنقضي به الدعوى العمومية، الأمر الذي يستدعي تسليط الضوء على هذا الطرف –الوسيط- من حيث الجهة المسندة إليها هذه المهمة وشروطه ونطاق صلاحيته في التشريعين الجزائري والفرنسي، هذا الأخير الذي كان سباقا في تنظيمها مقارنة بالتجربة الجزائرية التي لا تزال في بدايتها، وقصدنا دراسة الأحكام القانونية المتعلقة بالوسيط في التشريعين الجزائري والفرنسي، لإجراء موازنة بين النظامين، أين سيتضح من خلالها مدى مواكبة المشرع الجزائري للتطور الحاصل في هذا المجال لتفعيل دور الوسيط ومن ثم نجاح الوساطة كطريق بديل لحل النزاعات الجزائية. Abstract: Under Order No. (02/15) of 23/07/2015, which amends the Code of penal procedures, and the Code of the Child protection N°( 12/15) of 15/07/2015, The Algerian legislature introduced the mediation system as a new mechanism to resolve disputes in some penal laws, in keeping with both commonlaw legislation or romano- germanic legislation, which was recognized long time ago. The mediation process consisits of three parties, the victim, the offender and the mediator, the latter, which is entrusted with the task to administrate the proccess, trying to bring closer the viewpoints of both sides to reach an agreement to end the conflict and close the public case. It is necessary to shed light on this party- the mediator. In terms of the assigned person to this task , the conditions and the scope of his or her validity in the Algerian and the French legislation. The latter, who had the lead in organizing it, in comparison to the Algerian experience which is still in the beginning. We intented to study the legal provisions related to the mediator in Algerian and the French legislation, to balance between the two systems, where only then, it will be clear to what extent he Algerian legislature is keeping pace with the development in this matter, in order to activate the role of mediator, as a successful alternative way to resolve conflicts and penal disputes.
Keywords: الوسيط؛ النزاعات الجزائية؛ الاختصاص؛ سلطة الملاءمة؛ الرقابة